1999
DOI: 10.1002/1529-0131(199910)42:10<2060::aid-anr6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A new spin on an old model: In vivo evaluation of disease progression by magnetic resonance imaging with respect to standard inflammatory parameters and histopathology in the adjuvant arthritic rat

Abstract: MRI can be used to noninvasively detect, monitor, and quantify the chronic synovitis and progressive destruction of soft tissue and bone in live AIA rats, thereby improving the ability to evaluate disease progression in this preclinical animal model of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Adjuvant arthritis is very similar to human RA both in pathological and serological changes. 25) In this study, we found that all rats swelled and appeared red in the injected ankle on day 2, after complete Freund adjuvant injection. On day 7, the injected rats displayed secondary in‰ammation on the left hindpaw and forelimbs.…”
Section: Discussionsupporting
confidence: 50%
“…Adjuvant arthritis is very similar to human RA both in pathological and serological changes. 25) In this study, we found that all rats swelled and appeared red in the injected ankle on day 2, after complete Freund adjuvant injection. On day 7, the injected rats displayed secondary in‰ammation on the left hindpaw and forelimbs.…”
Section: Discussionsupporting
confidence: 50%
“…Evaluation of antirheumatic drugs on adjuvant-induced arthritis (AIA) has been performed on the basis of indicators such as paw swelling, clinical score, histopathology, X-radiography and recently magnetic resonance imaging (MRI) [13,14]. An antimetabolite, MTX has been reported to be effective in suppressing development of AIA [15 -17].…”
Section: Introductionmentioning
confidence: 99%
“…The established model exhibits pronounced soft tissue and synovial inflammation between day 16 and 30 and is accompanied by a marked progression of periosteal reactions, pannus formation, internal bone inflammation, fibrosis in the joints, and end-stage ankylosis (Weichman, 1989). Classical paw edema measurements were made as well as examinations of paw architecture using MRI techniques described by us (Jacobson et al, 1999). Daily oral doses of ABT-963 from days 14 to 28 gave significant inhibition of paw swelling as measured by plethysmography and MRI.…”
Section: Cox-2 Inhibitors 909mentioning
confidence: 99%
“…Paw edema was evaluated for significance from control adjuvant edema using Dunnett's multiple comparison test where p Ͻ 0.05 was considered statistically significant. MRI images were taken at initiation of dosing and after the last dose (Jacobson et al, 1999).…”
mentioning
confidence: 99%